2012
DOI: 10.5194/bgd-9-10057-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of soil greenhouse gas fluxes from extensive and intensive grazing in a temperate maritime climate

Abstract: Greenhouse gas (GHG) fluxes from a seminatural, extensively sheep grazed drained moorland and intensively sheep grazed fertilised grassland in SE Scotland were compared over 4 yr (2007–2010). Nitrous oxide and CH<sub>4</sub> fluxes were measured by static chambers, respiration from soil including ground vegetation by a flow through chamber and the net ecosystem exchange of CO<sub>2</sub> by eddy covariance. All GHG fluxes displayed high temporal and interannual variability. Tempe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…According to the median values, the G5 site reached the highest amount of C sequestration (~113.7 g C m −2 yr −1 ) at LD 50 N 0 . The general observation from the modelled sites of increasingly negative NEE in response to increasing N inputs is consistent with experimental observations that report increases in the flow of C to the soil in response to long-term fertilizer N use Skiba et al, 2013). For the period during which the C is sequestered, it is removed from the atmosphere and does not contribute to global warming.…”
Section: Co 2 Fluxessupporting
confidence: 87%
“…According to the median values, the G5 site reached the highest amount of C sequestration (~113.7 g C m −2 yr −1 ) at LD 50 N 0 . The general observation from the modelled sites of increasingly negative NEE in response to increasing N inputs is consistent with experimental observations that report increases in the flow of C to the soil in response to long-term fertilizer N use Skiba et al, 2013). For the period during which the C is sequestered, it is removed from the atmosphere and does not contribute to global warming.…”
Section: Co 2 Fluxessupporting
confidence: 87%
“…Nitrous oxide emissions are influenced by both management and environmental conditions (Flechard et al, 2007, Bell et al, 2015Cowan et al, 2015). In our study N 2 O fluxes showed typical temporal variations with high N 2 O peaks after N application decreasing to background levels after < 1 to 20 days, increased losses during wetter periods, and reduced losses during the colder winter months (Skiba et al, 2013). Spatial variability was high due to the uneven distribution of excreta and urine and uneven soil compaction from grazing animals .…”
Section: N Loss To the Environmentmentioning
confidence: 54%
“…The DELTA system comprised of a denuder filter sampling train, an air pump (providing a sampling flow rate of 0.2-0.4 L min -1 ) and a high sensitivity dry gas meter to record sampled volumes (Tang et al, 2009) set at 1.5 m height above ground. N dry deposition fluxes were calculated using the average flux from four different inferential models; the UK CBED scheme (Concentration Based Estimated Deposition technique (Smith et al, 2000), the Dutch IDEM model (Bleeker, 2000), (Erisman et al, 1994), the dry deposition module of the Environment Canada model CDRY (Zhang et al, 2001;Zhang et al, 2003) and the surface exchange scheme EMEP (Simpson et al, 2003;Tuovinen et al, 2009), as described in detail by Flechard et al were measured using manual closed static chambers (Clayton et al,1994, Skiba et al, 2013 .…”
Section: Nitrogen and Carbon Leaching (Fn Leaching + Fc Leaching )mentioning
confidence: 99%
“…Fertilizer addition is another management factor that affects the carbon dynamics in tea plantations, which will stimulate plant growth and microbial activity (Ammann, Flechard, Leifeld, Neftel, & Fuhrer, ; Schmitt, Bahn, Wohlfahrt, Tappeiner, & Cernusca, ; Skiba et al, ; Zeeman et al, ). Multiple studies reported that fertilizer additions will increase carbon uptakes (Eze et al, ; Moinet et al, ; Peichl, Leahy, & Kiely, ) or inhibit soil respiration and microbial respiration (Bowden, Davidson, Savage, Arabia, & Steudler, ; Janssens et al, ; Olsson, Linder, Giesler, & Hogberg, ; Ramirez, Craine, & Fierer, ), but other studies reported that the addition of N fertilizer results in a large carbon loss by the increase in soil microbial activity (Fang et al, ).…”
Section: Discussionmentioning
confidence: 99%